Manajemen Dana Desa (Studi: Desa Abason Kecamatan Totikum Kabupaten Banggai Kepulauan) - Pratiwi, Arum; Suasa; Afandi, Muhammad (JPS: Journal of Publicness Studies, 2025)
Management in Abason Village by activity implementers is not yet fully effective. This can be seen in the Village Fund planning process, the community has not fully participated or the community has not been involved enough in both the planning and implementation processes. The process of organizing the structure and management of village funds is not yet optimal because their human resources are determined not to match their capabilities In the actuating process in moving village officials to complete their duties and responsibilities in accordance with community needs, the programs implemented have not run optimally, such as development programs that have not been on target. And the controlling process is still weak, this can be indicated by the transparency of the Village government which is still closed, resulting in a lot of criticism from the community.